Youth for disaster preparedness a communication plan for NYP-09-12-03 - Tripoli, Keinne Ross C.
In our current society, various calamities and disasters had been experienced by people especially Filipinos due to some erratic changes of weather or so-called global warming. As such, these phenomenons had caused the youth leaders in creating of NYP-09-12-03 also known as a Resolution to Strengthen Participation of the Youth Sector in the Planning, Information Dissemination, Implementation and Monitoring of the Disaster Risk Management Plans of Local Government Units in the Philippines which encourages youth to be part of the Disaster Risk Reduction planning and implementation. The existence of this resolution paved way to the need for youth to be involved in such circumstances. The researcher then decided to create a communication plan that would help package and deliver the message ?youth involvement in the context of Disaster Preparedness? to the intended audience, the youth sector. This sector were further segmented into Out-of-School youth represented by Pag-asa Youth Association of the Philippines (PYAP) and Red Cross ? Davao Chapter and had undergone further profiling based from their knowledge, attitude and practices regarding disaster, disaster preparedness and youth involvement. Furthermore, these organizations had undergone audience analysis through SWOT Analysis. Through the profiling and analysis of the mentioned organizations and with the help of Social Marketing as the study?s framework, this intends to formulate a general communication plan consisting of various Information, Education and Communication Strategies as well as Monitoring and Evaluation Framework that can be adapted and implemented by the said stakeholders per se.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication